Analytical modeling of MHD flow over a permeable rotating disk in the presence of soret and dufour effects: Entropy analysis. - Freidoonimehr, N.; Rashidi, M.M.; Abelman, S.; Lorenzini, G. (MDPI AG, 2016)
The main concern of the present article is to study steady magnetohydrodynamics (MHD) flow, heat transfer and entropy generation past a permeable rotating disk using a semi numerical/analytical method named Homotopy Analysis Method (HAM). The results of the present study are compared with numerical quadrature solutions employing a shooting technique with excellent correlation in special cases. The entropy generation equation is derived as a function of velocity, temperature and concentration gradients. Effects of flow physical parameters including magnetic interaction parameter, suction parameter, Prandtl number, Schmidt number, Soret and Dufour number on the fluid velocity, temperature and concentration distributions as well as entropy generation number are analysed and discussed in detail. Results show that increasing the Soret number or decreasing the Dufour number tends to decrease the temperature distribution while the concentration distribution is enhanced. The averaged entropy generation number increases with increasing magnetic interaction parameter, suction parameter, Prandtl number, and Schmidt number.
Keywords: Dufour effect; Entropy generation; HAM; Heat and mass transfer; MHD flow; Rotating disk; Soret effect